EFFECT OF SEASONAL ON NUTRIENT LOAD INPUT THE INNER AMBON BAY - F.S. Pello; E.M. Adiwilaga; N.V. Huliselan; A. Damar (Bumi Lestari Journal of Environment, 2014)
Input nutrients into the Inner Ambon Bay very influenced by season. Activity in the bay and input nutrients from land and  outer Ambon Bay as well as the influence of upwelling in  Bandasea could increase eutrophication in the bay. This study aimed to analyze the influence of freshwater and  the exchange of sea water to the concentration of nutrients in  Inner AmbonBay. The study was conducted from June 2011 to May 2012. Average content of nitrate in East season (0.04 to 2.36 µM (0.57±0.78), Transition Season II 0.05 to 2.20 µM (0.36±0.67); andTransition Season I0.09 to 1.66 µM (0.59±0.47) are higher while the West season 0.05-0.10µM (0.06±0.02) is lower than the water quality standard for marine biota. Average value of phosphatein the four seasons is higher than the sea water quality standard, while enter nitrate and phosphates from Outer Ambon Bay in the East Season is larger than from river. Temporally andspatially condition of Inner Ambon Bay are oligotrophic and mesotrophic. Flushing time in Inner Ambon Bay is 14 days.